Mystery of the megavolcano [videorecording (DVD)] - Fox, Ben (WGBH Boston Video, 2007)
In a classic science detective story, Nova pieces together the clues about this great catastrophe and probes questions raised about human evolution and Earth's fragile ecosystems.